Stress Coping in Mothers Who Accompany Elementary School Children to Learn From Home During the Covid-19 Pandemic - Putri, Ida Ayu Yolandy; Lerik, M. Dinah Charlota; Damayanti, Yeni (Journal of Health and Behavioral Science, 2023)
COVID-19, or severe acute respiratory syndrome coronavirus 2 (SARS_CoV- 2), is a virus that attacks the respiratory system. COVID-19 significantly impacts society's survival, one of which is the world of education, so education must be replaced with online learning methods. Many parents feel overwhelmed because they must do many jobs, so stress arises for parents. Ways to solve problems require coping strategies. This study aimed to determine the description of stress coping of mothers who accompany elementary school children to study from home during the COVID-19 pandemic at SD Kristen Citra Bangsa Mandiri. This type of research is quantitative descriptive research. The population in this study were 571 parents of grades 2-6. The sampling technique was purposive, with a total sample size of 232 mothers. The results showed that while accompanying children learning online from home, the stress coping used by mothers was emotion-focused coping, and the dominant aspect used by mothers was the positive reappraisal aspect. It is hoped that mothers who have children who study with online learning can divide their time well between home or office work and accompanying children to study online. The school can also make webinars or workshops for parents related to parenting and can also talk about child mentoring.